2015 IEEE Custom Integrated Circuits Conference (CICC) 2015
DOI: 10.1109/cicc.2015.7338371
|View full text |Cite
|
Sign up to set email alerts
|

A 1.8-pJ/bit 16×16-Gb/s source synchronous parallel interface in 32nm SOI CMOS with receiver redundancy for link recalibration

Abstract: A 16x16-Gb/s source-synchronous I/O is reported in 32nm SOI CMOS. The bus-level receiver includes redundant RX lanes to enable lane recalibration with reduced power and area overhead. The I/O also includes an 8:1 TX serializer with 8-phase clocking, and an active-inductor-based RX CTLE whose outputs form current mirrors with the inputs of the RX samplers. A phase rotator based on currentintegrating phase interpolator cores is described, with architecture and circuit improvements to performance as compared to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The signalling topology uses passive termination on the transmitter for equalization. Dickson et al showed source synchronous parallel links for chip to chip communication [20][21] [22]. For equalization at the receiver, decision feedback equalization (DFE) was implemented with infinite impulse response (IIR) along with standard digital DFE.…”
Section: Die_0mentioning
confidence: 99%
“…The signalling topology uses passive termination on the transmitter for equalization. Dickson et al showed source synchronous parallel links for chip to chip communication [20][21] [22]. For equalization at the receiver, decision feedback equalization (DFE) was implemented with infinite impulse response (IIR) along with standard digital DFE.…”
Section: Die_0mentioning
confidence: 99%
“…To overcome the metastability problem, we can also implement a source synchronous interface [7], where the sending node sends its clock signal through a clock path to the receiving node. The sent clock signal is certainly used to synchronized the transmitted data.…”
Section: Related Work and The Key Featurementioning
confidence: 99%